Pengembangan Bahan Ajar Tematik dalam Implementasi Kurikulum 2013 Kelas 1 Sekolah Dasar - Illahi, Diah Permata; Nisa, Sahrun; Suriani, Ari (ALSYS, 2024)
The 2013 curriculum emphasizes learning through a series of topics. The objectives of this study are. To analyze the needs of teachers in implementing appropriate learning models based on the 2013 Curriculum, especially in elementary schools. To develop effective and efficient thematic learning materials on the topic of natural resources. To test the effectiveness of the developed learning model. Research Steps, Development of learning materials The research team developed thematic learning materials on the topic of natural resources. Four experts in the field of education provided input and suggestions to improve the first draft of the thematic textbooks. Trial of learning materials The revised learning materials were tested on elementary school students. The effectiveness of the learning model was measured using tests and data analysis. Research Results. The developed thematic learning materials were proven to be useful and effective in helping students understand natural resource materials. Students achieved a minimum mastery of learning of 72% and a classical mastery of 91.6%. Test results showed an increase in student learning scores after using the workbook.